2019
DOI: 10.1016/j.polymer.2019.121595
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity and secondary crystallisation kinetics in poly(lactic acid)

Abstract: The non-steady state technique of laser flash analysis (LFA) was used to record the variation of thermal diffusivity with time during the cold-crystallisation of poly(lactic acid), a grade containing 4% D stereoisomer content. The measured diffusivity data was analysed in terms of the Avrami and Hoffman-Lauritzen models for polymer crystallization. Within the temperature range 88 to 109C, mechanistic 'n' values of 2.0±0.1 were calculated and a nucleation constant of 6.58 x 10-5 K 2 was determined; the LFA tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…As far as the heat transport via the polymer was concerned, this was quite poor in the amorphous polymers and became worse when filler-polymer interfaces were involved [22,23]; the latter acting as heat scatterers. On the contrary, the formation of crystals (ordered structures) is known to favor polymerthrough transport of hot phonons [45,46]. This was clear in our case when comparing the amorphous and highly crystalline matrices in Figure 8.…”
Section: Thermal Conductivity (Lfa)mentioning
confidence: 59%
See 2 more Smart Citations
“…As far as the heat transport via the polymer was concerned, this was quite poor in the amorphous polymers and became worse when filler-polymer interfaces were involved [22,23]; the latter acting as heat scatterers. On the contrary, the formation of crystals (ordered structures) is known to favor polymerthrough transport of hot phonons [45,46]. This was clear in our case when comparing the amorphous and highly crystalline matrices in Figure 8.…”
Section: Thermal Conductivity (Lfa)mentioning
confidence: 59%
“…In the HDPE-based systems compared with the PS-based ones, α and λ were larger and this was most probably due to the implementation of polymer HDPE crystals at high fractions [22,33,45,46,71]. In Figure 8a, the % increase in CF was not equal or similar to the increase of α and λ.…”
Section: Thermal Conductivity (Lfa)mentioning
confidence: 89%
See 1 more Smart Citation
“…In a series of recent papers [22,26,28], it has been shown that the Avrami model can be modified to successfully account for a secondary crystallisation process. The modification is based on the idea that the secondary process develops with the square root of time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the thickness of the lamellae is greater at the centre of the spherulite, it was postulated that secondary crystallisation occurs as soon as the lamellae has been formed and proceeds with and beyond the primary process [22]. These factors have led to the formation of a new model for the crystallisation of polymers, which has been validated using infra-red spectroscopy [22,26] and laser flash analysis [28].…”
Section: Introductionmentioning
confidence: 99%